Community perceptions of the social and economic impacts of COVID-19 in Myanmar: Insights from a National COVID-19 Community Survey (NCCS) - June and July 2020 - Lambrecht, Isabel B.; Headey, Derek D.; Oo, Than Zaw; Goudet, Sophie (International Food Policy Research Institute, 2020)
Myanmar has been fortunate in thus far having one of the lowest caseloads of COVID-19 per population globally, with under 400 confirmed cases as of early August. However, as a developing economy still beset by high rates of poverty and vulnerability, Myanmar is highly susceptible to the economic and social disruptions stemming from COVID-19. These disruptions began with the closure of the Chinese border and the cessation of agricultural exports in late January, followed in February and March by further disruptions to trade, tourism, manufacturing, and remittances. However, an economic simulation analysis by Diao et al. (2020) suggests that the most severe economic impacts of COVID-19 stemmed from the temporary lockdown policies imposed in late March, which – though necessary to prevent the further spread of the virus – led to significant disruptions throughout the economy, including the agri-food sector and the rural economy. Phone survey evidence on agricultural and industrial value chains demonstrates that economic disruptions related to COVID-19 are pervasive and significant (Fang et al, 2020; Goeb, Boughton, and Maredia 2020; Goeb et al. 2020, Takeshima, Win, and Masias 2020a, 2020b). In aggregate, economic simulations predict a modest contraction in Myanmar’s gross domestic product in 2020 (compared to rapid growth forecasted in the absence of COVID-19), but a more significant reduction in household incomes at around 12 percent on average.